Breast phantom for comparison X-ray and polarimetric optical tomography imaging - Sobotka, Piotr Kamil; Chełmiński, Krzysztof; Bulski, Wojciech; Kacperski, Krzysztof; Dziukowa, Janina; Wesołowska, Ewa; Wieczorek, Szymon; Miernicki, Sławomir; Budaszewski, Daniel; Woliński, Tomasz; et al. (Photonics Letters of Poland, 2012)
Breast phantom made as combination of paraffin and INTRALIPIDTM was tested by use of conventional X-ray computed tomography and polarimetric optical tomography. The INTRALIPIDTM is a liquid commonly used for simulation breast tissues optical properties but it is useless as X-ray phantom. During our tests we have observed that X-ray tomography allows to reconstruct correctly the positions of INTRALIPIDTM inclusions inside paraffin medium but we cannot distinguish different densities of INTRALIPIDTM in each inclusion. On the other hand the polarimetric optical tomography allows to distinguish densities of INTRALIPIDTM (0%, 10%, 20%) in inclusions but with relatively low accuracy of their position. Full Text: PDF References Stanton L., Villafana T., Day J. L. and Lightfoot D. A., "A breast phantom method for evaluating mammography technique", Invest Radiol. Vol. 13, No. 4, (1978)[CrossRef] Obenauer S., Hermann K. P. and Grabbe E., "Dose reduction in full-field digital mammography an anthropomorphic breast phantom study", Br J Radiol Vol. 76, No. 907, (2003)[CrossRef] F. A. R. Silva, L. F. Souza, C. E. G. Salmon and D. N. Suoza, "Breast phantom with silicone implant for evaluation in conventional mammography", JACMP, Vol. 12, No. 1 (2011) M. Yakabe, S. Sakai, H. Yabuuchi, Y. Matsuo, T. Kamitani, T. Setoguchi, M. Cho, M. Masuda, and M. Sasaki, "Effect of Dose Reduction on the Ability of Digital Mammography to Detect Simulated Microcalcifications", J. Digit. Imaging, Vol. 23 No.5, (2010)[CrossRef] E.B. Haller, "Time-resolved transillumination and optical tomography",J. Biomed. Opt., Vol. 1, No. 1, (1996) Tarvainen, T., Vauhkonen, M., Kolehmainen,V., Kaipio, J. P. and Arridge S. R., "Utilizing the Radiative Transfer Equation in Optical Tomography", PIERS Online, Vol. 4, No. 6, (2008)[CrossRef] Huang, D. E., Swanson, A. C., Lin, P., Schuman, J. S., Stinson, W. G., Chang, W. M., Hee, R., Flotte, Gregory, T. K., Puliafito, C. A. and jimoto, J. G., „Optical coherent tomography”, Science 254, (1991) Fercher, A. F., Drexler , W., Hitzenberger, C. K. and Lasser, T., „Optical coherence tomography—principles and applications”, Rep. Prog. Phys. 66, (2003) Bajraszewski, T., Gorczyńska, I., Szkulmowska, A., Szkulmowski, M., Targowski P. and Kowalczyk, A. „Spectral Optical Coherence Tomography in ophthalmology”, Proceedings of SPIE 5959, (2005) Nielsen, T., Brendel, B., Ziegler, R., Beek, M., Uhlemann, F., Bontus, C. and Koehler, T., "Linear image reconstruction for a diffuse optical mammography system in a noncompressed geometry using scattering fluid", Applied Optics, Vol. 48, No. 10, (2009)[CrossRef] P. Sawosz, M. Kacprzak, N. Zolek, W. Weigl, S. Wojtkiewicz, R. Maniewski, A. Liebert, "Optical system based on time-gated, intensified charge-coupled device camera for brain imaging studies", J. Biomed. Opt., Vol. 15, No. 6, (2010)[CrossRef] S. Srinivasan, B. W. Pogue, H. Dehghani, S. Jiang, X. Song, K. D. Paulsen, "Improved quantification of small objects in near-infrared diffuse optical tomography", J. Biomed. Opt., Vol. 9, No. 6, (2004)[CrossRef] Hielscher, A. H., Klose, A. D. and Hanson, K. M., "Gradient-Based Iterative Image Reconstruction Scheme for Time-Resolved Optical Tomography ", IEEE Transactions on Medical Imaging Vol. 18, No. 3, (1999)[CrossRef] J. C. Hebden, B. D. Price, A. D. Gibson and G. Royle, "A soft deformable tissue-equivalent phantom for diffuse optical tomography", Phys. Med. Biol., Vol. 51, (2006)[CrossRef] Ghosh, N., Woods,M. F. G., Li, S. H., Weisel, R. D. and Wilson, B. C., L. Ren-Ke, I. A. Vitkin, „Mueller matrix decomposition for polarized light assessment of biological tissue”, Journal of Biophotonics, Vol. 2, No. 3, (2009) Domanski, A. W., Rytel, M. and Wolinski, T. R., "Polarization optical tomography based on analysis of Mueller matrix elements of scattered light", Proceedings of SPIE Vol. 5959, (2005)[CrossRef] S. Miernicki, P. K. Sobotka, A. W. Domański, "Comparison of polarization and polarimetric optical tomography methods for recognition of tissue simulators inside breast phantom", Phot. Lett. Poland, Vol. 3, No 4 (2011)[CrossRef] M. Born, E. Wolf, “Principles of Optics: Electromagnetic Theory of Propagation, Interference and Diffraction of Light”, 6th ed., (1997) Xu, T., Zhang C., Wang X., Zhang L. and Tian J., "Measurement and analysis of light distribution in intralipid-10% at 650 nm", Applied Optics, Vol. 42, No. 28, (2003)[CrossRef] S.T. Flock, S.L. Jacques, B.C. Wilson, W.M. Star, M.J.C. van Gemert, "Optical Properties of Intralipid: A phantom medium for light propagation studies", Lasers in Surgery and Medicine, Vol. 12, pp. 510-519, (1992)[CrossRef] R. Srinivasan, D. Kumar, M. Singh, "Optical tissue-equivalent phantoms for medical imaging", Trends Biomater. Artif. Organs. , vol. 15, No. 4, (2002)